2019
DOI: 10.36740/wlek201908111
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Adipocyte Secretion Disorders in Patients With Non-Alcoholic Fatty Liver Disease With Overweight and Obesity

Abstract: Introduction: The attention of scientists from many countries is focused on hormonal substances - adipokines at the present time. Lowering the level of the hormone adiponectin plays a central role in the development of obesity and cardiovascular disease in humans. The aim of the work is to determine the effect of complex therapy of thiotriazolin and L-lysine escinate on adipocyte secretion indices in patients with non-alcoholic fatty liver disease (NAFLD) with overweight and obesity. Materials and methods: 135… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
5
0
4
Order By: Relevance
“…Until now, a lot of substances secreted by adipose tissue have been discovered and described, and their metabolic effects and contribution to the pathogenesis of civilization-related diseases are being extensively studied [39][40][41][42]. It is interesting that both obese and lipodystrophic patients show similar clinical disorders: hypertriglyceridemia, insulin resistance and fatty liver [43][44][45]. The disorders lead to diabetes, hypertension, polycystic ovary syndrome (PCOS), coronary artery disease (CAD) and cancers [45][46][47][48][49][50].…”
Section: Adipokines and Metabolic Disordersmentioning
confidence: 99%
“…Until now, a lot of substances secreted by adipose tissue have been discovered and described, and their metabolic effects and contribution to the pathogenesis of civilization-related diseases are being extensively studied [39][40][41][42]. It is interesting that both obese and lipodystrophic patients show similar clinical disorders: hypertriglyceridemia, insulin resistance and fatty liver [43][44][45]. The disorders lead to diabetes, hypertension, polycystic ovary syndrome (PCOS), coronary artery disease (CAD) and cancers [45][46][47][48][49][50].…”
Section: Adipokines and Metabolic Disordersmentioning
confidence: 99%
“…Adiponectin has also been shown to prevent endothelial apoptosis. We found that in patients with NAFLD with overweight and obesity, increased leptin levels, decreased serum adiponectin levels were associated with increased body mass index, insulin resistance, increased concentration of highly sensitive CRP [12].…”
mentioning
confidence: 75%
“…Свій вклад вносить і метаболічний статус [20,21] Ми виявили, що у пацієнтів з НАЖХП із надмірною масою тіла та ожирінням підвищення рівня лептину, зниження рівня адипонектину в сироватці крові мали зв'язок з підвищенням індексу маси тіла, інсулінорезистентністю [22]. При надмірній масі тіла проліферація та гіпертрофія адипоцитів супроводжується інфільтрацією макрофагами з подальшим розвитком запальних реакцій, внаслідок чого змінюється метаболічна активність жирової тканини [23,24].…”
Section: шевчук тетяна валентинівнаunclassified